Palladium(II) and Platinum(II) Bis(Stibinidene) Complexes with Intramolecular Hydrogen-Bond Enforced Geometries - Zechovský, Jan; Kertész, Erik; Erben, Milan; Hejda, Martin; Jambor, Roman; Růžička, Aleš; Benkő, Zoltán; Dostál, Libor (ChemPlusChem, 2024)
The coordination capability of two N,C,N pincer coordinated stibinidenes, i. e. bis(imino)- [2,6-(DippN=CH)2C6H3]Sb (1) or imino-amino- [2-(DippN=CH)-6-(DippNHCH2)C6H3]Sb (2) toward palladium(II) and platinum(II) centers was examined. In the course of this study, seven new square-planar bis(stibinidene) complexes were synthesized and characterized by NMR, IR, Raman, UV-vis spectroscopy and single crystal (sc)-X-ray diffraction analysis. In all cases, both stibinidene ligands 1 or 2 adopt trans positions, but differ significantly in the torsion angle describing mutual orientation of aromatic rings of the stibinidenes along the Sb-Pd/Pt-Sb axes. Furthermore, majority of complexes form isomers in solution most probably due to a hindered rotation around Sb-Pd/Pt bonds caused by bulkiness of 1 and 2. This phenomenon also seems to be influenced by the absence/presence of a pendant -CH2NH- group in 1/2 that is able to form intramolecular hydrogen bonds with the adjacent chlorine atom(s) attached to the metal centers. The whole problem was subjected to a theoretical study focusing on the role of hydrogen bonds in structure architecture of the complexes. To describe the UV-vis spectra of these highly coloured complexes, TD-DFT calculations were employed. These outline differences between the stibinidene ligands, the transition metals as well as between the charge of the complexes (neutral or anionic).
Keywords: stibinidene; platinum; TD-DFT; hydrogen-bond; palladium